A new species of Corydoras Lacépède (Siluriformes: Callichthyidae) from the Rio Tapajós basin and its phylogenetic implications - Espíndola, Vinicius C.; Spencer, Marcelo R.S.; Rocha, Leandro R.; Britto, Marcelo R. (Papéis Avulsos de Zoologia, 2014)
A new species of Corydoras is described from tributaries of the rio Arinos, rio Teles Pires and rio Preto, all in the rio Tapajós basin. The new species is a member of a group that includes 36 species with spots on the body. Within this group, the new species can be readily distinguished by having a smaller dorsal-fin spine than the first three subsequent soft dorsal-fin rays; pectoral, pelvic and anal fins hyaline; dorsal-fin interradial membrane hyaline; rounded spots on trunk restricted to dorsolateral body plates and dorsal portion of ventrolateral body plates, not reaching the base of pelvic and anal fins. The new species can be further distinguished from Corydoras xinguensis by having spots with diffuse edges, and from all other species of spotted Corydoras except C.multimaculatus, by the absence of ventral platelets. A phylogenetic analysis recovered the new species plus Corydoras metae and C.araguaiensis in a clade sharing the presence of a pointed process on the maxilla for insertion of the retractor tentaculi muscle. In addition, the presence in the new species of an elongated anterior portion of the mesethmoid and a triangular uncinate process of the epibranchial 3 suggests a close relationship with Corydoras metae.